Analisis Hasil Belajar Fisika Terhadap Penerapan Strategi Pembelajaran Arcs Ditinjau Dari Motivasi Belajar Peserta Didik Kelas XI MIPA SMA Negeri 2 Majene - Sutrisno Sutrisno (Journal on Education, 2021)
This research is a true experiment using a 2×2 factorial design which was carried out in class XI MIPA1 and XI MIPA3 SMAN 2 Majene Kab. Majene. Data collection in this study was carried out in three stages, namely; 1) the preparation stage, 2) the implementation stage, 3) the final stage by giving a final test of physics learning outcomes which is then analyzed to test the hypothesis. The results of hypothesis testing were carried out using two-way analysis of variance which showed that (1) there were differences in physics learning outcomes between students taught through the ARCS learning strategy and those taught using conventional learning, (2) for high learning motivation, there was a difference between the results learning physics of students who are taught using the ARCS learning strategy with students who are taught with conventional learning, (3) for low learning motivation, there is a difference between the physics learning outcomes of students who are taught using the ARCS learning strategy with students who are taught with conventional learning, and ( 4) there is an interaction effect between learning strategies and learning motivation on the achievement of physics learning outcomes, in class XI MIPA students at SMAN 2 Majene.